2020
DOI: 10.1002/ptr.6701
|View full text |Cite
|
Sign up to set email alerts
|

Herbal treatments for migraine: A systematic review of randomised‐controlled studies

Abstract: Herbal treatments are often used as a treatment for migraine. Therefore, an evaluation of their safety and efficacy is important. Based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, and Cochrane Collaboration's tool for assessing the risk of bias, a systematic literature review of randomised, controlled human trials assessing the effects of herbal treatments delivered as a single ingredient for the acute or prophylactic treatment of migraine were conducted. Studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 107 publications
0
26
0
1
Order By: Relevance
“…Feverfew has been used in traditional and folk medicine for the treatment of fever, cold, asthma, migraine headache, arthritis, women's health issues, inflammatory conditions, and so on (George et al, 2012;Pareek et al, 2011). Although the qualitative standard of many trials in the phytopharmacological field are less rigorous than the conventional pharmaceutical sector (Williamson, Liu, & Izzo, 2020), clinical evidence suggests that feverfew extract might have positive results in migraine prevention (Lopresti, Smith, & Drummond, 2020). Phytochemical studies have shown the presence of many active ingredients of feverfew, including sesquiterpene lactones, flavonoid glycosides, sesquiterpenes, and monoterpenes.…”
Section: Cytokine Storm In Covid-19 and Parthenolide: Preclinical Evimentioning
confidence: 99%
“…Feverfew has been used in traditional and folk medicine for the treatment of fever, cold, asthma, migraine headache, arthritis, women's health issues, inflammatory conditions, and so on (George et al, 2012;Pareek et al, 2011). Although the qualitative standard of many trials in the phytopharmacological field are less rigorous than the conventional pharmaceutical sector (Williamson, Liu, & Izzo, 2020), clinical evidence suggests that feverfew extract might have positive results in migraine prevention (Lopresti, Smith, & Drummond, 2020). Phytochemical studies have shown the presence of many active ingredients of feverfew, including sesquiterpene lactones, flavonoid glycosides, sesquiterpenes, and monoterpenes.…”
Section: Cytokine Storm In Covid-19 and Parthenolide: Preclinical Evimentioning
confidence: 99%
“…Several herbal medicines, via their multifactorial physiological influences, represent potential options for the treatment of migraine (Lopresti, Smith, & Drummond, 2020). One of such remedies is ginger, which has shown very preliminary evidence of efficacy in the treatment (but not in the prevention) of mild migraine.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Botanical drugs have been widely used in the treatment of migraine attacks ( Hou et al, 2017 ; Lopresti et al, 2020 ). Conioselinum anthriscoides “Chuanxiong” (Apiaceae; Chuanxiong rhizoma) (known as Chuanxiong rhizoma in Chinese) is used to treat migraine and cerebral ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%